Three new species of Tellina (Bivalvia, Tellinidae) from the Panamic Province - Coan, Eugene V.; Valentich-Scott, Paul (Zootaxa, 2010)
In preparing a manual on the marine bivalves of the Panamic Province, we have found three species of the Tellinidae that lack names. The purpose of this paper is to describe a new species of Tellina (Hertellina), a new species of Tellina (Merisca), and a new species of Tellina (Acorylus). The subgenus Acorylus is reported for the first time from the eastern Pacific Ocean.